ACTUALIZATION KAMMI ROLE IN ISLAMIC VALUES IN STUDENTS FACULTY OF SOCIAL AND POLITICAL SCIENCE UNIVERSITY DIPONEGORO - Fakhri Muhammad; Susilo Utomo; Turtiantoro Turtiantoro (Journal of Politic and Government Studies, 2015)
KAMMI is a student movement which emphasizes the values of Islam, therefore besides politics KAMMI also have a dakwah purpose, namely to urge people to return to the path of Allah. As with any social movement, KAMMI also has a goal to change the values that exist in the society, which makes the surrounding society to cling to the values of Islam kaffah. This phenomenon is commonly called the Islamization, namely the return to Islamic values. It is also felt in the area FISIP Undip, which is KAMMI exist there. From this, the researchers will try to investigate what role KAMMI the process of Islamization in Undip FISIP students, as well as how the Islamisation process can be happen.The purpose of this study to determine how the role of KAMMI as extra movement campus campus KAMMI againts process of Islamization in the Faculty of Social and Political Sciences, University of Diponegoro (Diponegoro University), and how the process of Islamization that can happen. This study is a qualitative research. This type of research used in this research is descriptive analytic. Data retrieved through the interview process and document data KAMMI FISIP Undip, BEM FISIP Undip, and UPK FKMM.Based on this research, it is known that KAMMI role in the process of Islamization in FISIP Undip through several stages. The first is to strengthen the cadre, which is looking to be a cadre of potential students were then given the provisions of Islam that will be ready to plunge into FISIP student life can be exemplary role model for other students. The regeneration process is divided into formal cadre consisting of levels Daurah Marhalah (DM) 1 to Daurah Marhalah (DM) 3 to officially become a cadre KAMMI. There was also an informal cadre namely through the liqo or Halaqah. The channel is spread dakwah KAMMI today is through BEM FISIP Undip and also FKMM the container KAMMI in intra-campus institution. Although not optimal, but now has a chance KAMMI large enough to spread his message to the students FISIP Undip.Research has been done to provide information that in an effort to make the process of Islamization, KAMMI using the cadres to be syi'ar goes to students FISIP Undip. However, it is a process that is not optimal, it is because not strong KAMMI in strengthening organizations of intra-campus in FISIP Undip, it is deemed necessary because of the similarity of the organization's vision intra existing in applying Islamic values, then it will be easier to deploy Islamic values to students FISIP Undip the other, so that the process of Islamization is running better.